JEJAK IDEOLOGI DALAM PEMIKIRAN SOEKARNO MUDA - Irfan Syah Amin; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study uses a qualitative method and raises social phenomena about the thoughts of the Proclamation figure namely Soekarno, in this study the writer raises the research with the formulation of the problem (1) What ideologies influence Young Soekarno's thoughts (2) How Young Soekarno's thoughts about Marhaenism, Nasamax and Democracy. The purpose of this research is to Analyze ideologies that influence young Soekarno and understand young Soekarno's thoughts about Marhaenism, Nasamax and Democracy. This study uses a type of literature study, to collect research data using Library Research data collection techniques. The results of this study explain the ideologies that have a big influence on Sukarno's thoughts, namely, Javaism, Socialism, Islam, Nationalism and Marxism and explain Sukarno's ideas at a young age namely, Marhenism, Nasamax and Democracy. H.O.S Tjokroaminoto was the most influential person in the process of forming young Sukarno's thoughts, the ideological influences transmitted by H.O. Tjokroaminoto to Sukarno included Islam, Socialism and Nationalism.From the results of this study can be concluded that young Soekarno studied a lot of ideologies and had influenced Soekarno's political thinking and had an impact on the thoughts expressed by young Sukarno. Marhaenism with its Socio-Nationalism and Socio-Democracy, Nasamax with its concept of unity, as well as mutual cooperation contained in the Soekarno-style in the Pancasila that prove Sukarno was a Democratic. Keywords: Soekarno Muda, Ideology, Political Thought, Marhaenism, Nasamax, Democracy.